Analisis Keterampilan Menulis Puisi Dengan Menggunakan Model Think Talk Write Di Sekolah Dasar - Rosalina Wahyu Prastika; Lilik Binti Mirnawati; Badruli Martati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This study aims to analyze poetry writing skills using the Think Talk Write learning model in elementary school students. Sources of data used in this study are books and journals related to poetry writing skills using the Think Talk Write learning model. The method used in this research is literature review. The research was conducted by collecting data using books, as well as various journals related to the required research variables. The analysis that has been carried out from several journals is to explain the advantages and disadvantages of the Think Talk Write learning model in students' poetry writing skills in elementary schools. Based on the analysis of ten articles of the Think Talk Write (TTW) learning model, the lowest percentage value is 2.25% and the highest is 36%. Think Talk Write learning model can help develop children's creativity and develop imagination.